Optical and photoelectrical properties of the tetrathiotetracene-fullerene (TTTC₆₀) film heterostructures - Gorishny, M.P.; Verbitsky, A.B.; Kovalchuk, A.V.; Kovalchuk, T.N.; Lutsyk, P.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The optical and photoelectrical properties of heterostructures (HS)
SnO₂ТTTC₆₀Ag are investigated. The additional absorption of HS ТTT and C₆₀ is
revealed in comparison with those for their components, which testifies to the formation
of complexes between the ТTT and C₆₀ molecules near the ТTT-C₆₀ interface. Currentvoltage
characteristics (J-V) of a dark current is symmetric, as well as corresponds to the
Ohm law for the voltages of 0 to 0.4 V. In the voltage range of 0.4 to 1.0 V, the branch of
J-V at the positive polarity (I₊) goes above that at the negative polarity (I₋) at a SnO₂-
electrode. Thus, in the double logarithmic scale, I₊ and I₋ are described by direct lines
with the angular factors 1.77 and 1.37, accordingly, and exponents in the half-logarithmic
coordinates (log I−U). The open-circuit voltage Voc has a positive polarity at the SnO₂-
electrode irrespective of the illumination direction of a sample. Photovoltage is caused by
antiblocking bends of bands for holes and electrons near the SnO₂- and Ag-electrodes of
ТTT and C₆₀ films, accordingly. The dark effective specific resistance of the HS
SnO₂ТTTC₆₀Ag is equal to 5·10⁷
Ohm·cm.